Rancang Bangun Alat Bantu Pemeriksaan Knee Joint pada Kasus Osteoarthritis - Bagus Dwi Handoko; Agung Bayu Pamungkas; Akhmad Haris Sulistiyadi (Jurnal Imejing Diagnostik (JImeD), 2021)
Background : The Knee joint is a hinge joint with a change formed by the two condyls of the femur that are jointed with the superior surface of the tibial tube. Radiographic examination of the knee joint on AP weight bearing and lateral weight bearing projections is a good projection in revealing joint gaps in the knee joint. The constraints on this examination are when patients who have little difficulty standing on one leg when doing lateral projection of weight bearing. So that a knee joint examination tool is needed in the case of osteoarthrithis.Methods : The purpose of this study was to describe the design, study the function tests and performance tests of knee joint hearing aids in the case of osteoarthrithis.This research is a type of experimental research with the design of a one shoot case study. Data collection is obtained by a check list of results of functional tests and performance test tools. The data obtained was assessed by Guttman's scale and conclusions and suggestions were drawn.This study produced a design in the form of a knee joint examination tool. The tool is made of stainless steel pipes, on a pedestal made of wooden boards, foam and cloth. Based on the calculation of the check list using the Guttman scale.Result: The function test results were 100% and the performance test results were 96%. Until the knee joint examination tool in the case of osteoarthrithis is said to be feasible to use.Conclusion : This knee joint examination aid has a number of parts, a pedestal made of wood sheets, adjustable footrests, and a patient's padded arms. The auxiliary framework uses a 3 cm diameter stainless steel pipe with a thickness of 1 mm. Based on the functional tests in the Radiology Installation of Prof. Dr. Margono Soekarjo Purwokerto obtained results 100% for knee joint examination in osteoarthritis cases with AP weight bearing projections and lateral weight bearing. Based on performance tests which involved 5 respondents who were radiographers were said to be very appropriate with a percentage of 96% with an excess of ease in operation, reducing the movement of patients, and helping the radiographers to produce informative radiographs.